2015
DOI: 10.1016/j.firesaf.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Fire design rules for load bearing cold-formed steel frame walls exposed to realistic design fire curves

Abstract: Keywords:Light gauge steel frame walls Realistic design fire curves Axial compression strength of studs Fire resistance rating Limiting temperature method Fire design rules Simplified design method a b s t r a c t Light gauge Steel Frame (LSF) walls are extensively used in the building industry due to the many advantages they provide over other wall systems. Although LSF walls have been used widely, fire design of LSF walls is based on approximate prescriptive methods based on limited fire tests. Also these fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Finally, attention is brought to works focused on Fire Safety Design and Management, such as (ARIYANAYAGAM; MAHENDRAN, 2015) which evaluated the potential of integrating fire safety into modern building design; and (ABNT, 2013) which presented fire design rules for cold-formed steel frame walls exposed to realistic design fire curves. The keywords defined by the author reflect the main focus and trend of the research on Fire Performance in buildings.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, attention is brought to works focused on Fire Safety Design and Management, such as (ARIYANAYAGAM; MAHENDRAN, 2015) which evaluated the potential of integrating fire safety into modern building design; and (ABNT, 2013) which presented fire design rules for cold-formed steel frame walls exposed to realistic design fire curves. The keywords defined by the author reflect the main focus and trend of the research on Fire Performance in buildings.…”
Section: Resultsmentioning
confidence: 99%
“…Steau et al [37] experimentally studied fire-resistant board structures that were exposed to standard fire in order to increase the FRL. Gunalan et al [38] experimentally studied the fire performance of load-bearing cold-formed steel wall panels under standard fire conditions, and Ariyanayagam and Mahendran [39] studied the same phenomena under realistic-design fire conditions and established fire design rules [40]. Ariyanayagam and Mahendran [41] also investigated the impact of cavity insulation on the fire resistance of LSF walls and found that the use of cavity insulation enhanced the FRL of non-load-bearing walls, although it considerably reduced that of load-bearing walls.…”
Section: Fire Performance Of Construction Materialsmentioning
confidence: 99%
“…Though the standard fire curve has been used for centuries to determine the FRL of building elements, the actual FRL of building components subjected to real fires are considerably less than those obtained from standard fire tests [40,47]. Hence, the ISO 834 standard fire test regulations are not suitable for evaluating the fire performance of 3D-printed concrete walls in terms of establishing the highest temperature and the corresponding time taken to reach this highest temperature level [50].…”
Section: Fire Performance Of Construction Materialsmentioning
confidence: 99%
“…Shahbazian and Wang [8] proposed a simple method for calculating the temperatures of the steel studs of the LSF walls exposed to fire. Mahendran et al [9][10][11][12] studied the fire performance of a new kind of LSF wall with an insulation layer placed externally between the plasterboards on both sides of the wall. Mahendran et al 3 [13,14] studied non-load-bearing LSF walls subjected to fire.…”
mentioning
confidence: 99%